ANALISIS PENGARUH KEBIJAKAN EKSEKUTIF TERHADAP KEPATUHAN WAJIB PAJAK SEBAGAI UPAYA MENDONGRAK PENERIMAAN NEGARA - Dito Aditia Darma Nasution (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The accountability of the government in spending tax revenues and tax administration reform may influence tax payer’s compliance. The study is mainly intended to discover whether or not this phenomenon exists in the case of Indonesia. The study employs Structural Equational Modelling (SEM) of data collected through surveys of taxpayers and tax authority employees. The results shows that when the government has accountably spent tax revenues to improve quality of living, the tax payers compliance increased. In additon, the study reveals that capability of tax authority to deter tax evasion and the tax payers satisfaction on the tax authority’s services significantly influence the Indonesian tax payers’ compliance. On the other hand, tax administration reform measured by improvement in the aspects of service quality, the efficiency of processing time, the capability of the human capital, effort on combating tax evasions, and the information technology used does not significantly affect tax payers’ satisfaction.